Primary Stability of Three Different Osteotomy Techniques in Medullary Bone: An in Vitro Study - Ferdinando Attanasio; Alessandro Antonelli; Ylenia Brancaccio; Fiorella Averta; Michele Mario Figliuzzi; Leonzio Fortunato; Amerigo Giudice (Dentistry Journal, 2020)
Background: The aim of this in vitro study was to analyse the primary stability of 20 implants placed with Twist drills (TD) versus 20 implants placed with Summers osteotomes (SO) and 20 implants placed with B&B bone compactors (BC) in medullary bone (quality type III and type IV). Methods: The implants were placed in 10 fresh pig ribs fixed on a bench vice in order to avoid micro-movements during surgical procedures and measure recording. Peak insertion torque (PIT) and Peak removal torque (PRT) were recorded with MGT-12 digital torque gauge and ISQ was recorded through OSSTELL ISQ™ device by an independent operator. Results: Comparing our data (Tukey test p = 0.05), it was evidenced a statistically significant difference in the PIT between TD and BC groups (p = 0.01). Analysing ISQ data, there was a statistically significant difference between the TD and BC groups (p = 0.0001) and between the SO and BC groups (p = 0.014). The analysis of PRT evidenced a statistically significant difference between the TD and BC groups (p = 0.038). Conclusions: This study evidenced that bone compactor preparation can positively influence primary implant stability (PS), however further in vivo studies and a larger sample are necessary to assess the usefulness in several clinical settings.